(untitled) (International Journal of Environmental Sciences, 2025)
The concept of employee engagement has been discussed and researched from many years. In this paper employee engagement based on O positive Blood group is discussed. Once you start studying about the O positive Blood group it becomes very essential to understand what factors are influencing O positive blood group labourer. For understanding employee engagement labours in manufacturing companies in Mysuru are studied. It is an empirical paper based on both primary and secondary data are used in the paper. Fifty convenient samples contract / permanent labours are studied in the paper. The statistical tool used in paper is SPSS Software. Reliability test and factor analysis are used to analyze the data. After the analyses 7seven factors influencing the employee engagement identified.They are compensation, Work Resources, Communication, and Supervisor, Role clarity, Team work, Innovation and change.